Regular Exercise, Subjective Wellbeing, and Internalizing Problems in Adolescence: Causality or Genetic Pleiotropy? - Bartels, Meike; De Moor, Marleen; Van der Aa, Niels; Boomsma, Dorret; De Geus, Eco (Frontiers in Genetics, 2012)
This study tests in a genetically informative design whether exercise behavior causally influences subjective wellbeing (SWB) and internalizing problems (INT). If exercise causally influences SWB and INT, genetic and environmental factors influencing exercise behavior will also influence SWB and INT. Furthermore, within genetically identical (MZ) twin pairs, the twin who exercises more should also show higher levels of SWB and lower levels of INT, than the co-twin who exercises less, because genetic confounding is excluded. Data on these phenotypes were available in a sample of 6,317 adolescent twins and 1,180 non-twin siblings. Most participants had longitudinal data with 2-year follow-up. Exercise behavior was cross-sectionally and longitudinally associated with fewer internalizing problems and increased SWB (correlations ranged from .12 to .16). Cross-sectional and longitudinal associations were mainly accounted for by genetic factors, whereas the contribution of environmental factors was negligible. Within MZ twin pairs, the twin who exercised more did not show fewer internalizing problems and increased SWB. This was found cross-sectionally and longitudinally. We conclude that exercise behavior is associated with fewer internalizing problems and higher levels of SWB. The association largely reflects the effects of common genetic factors on these traits.